Turmeric (Curcuma Longa Linn.) Supplementation as an Alternative to Antibiotics in Poultry Diets - Nanung Danar Dono (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2013)
Antibiotics have been used in non-therapeutic fashion as growth promoter for about 50 years in many parts of the world. It has been proven that supplementation of antibiotics in the diets reduces morbidity and mortality, as well as improve feed efficiency and overall growth performance of broiler chickens. However, the routine use of these antimicrobial growth promoters (AGPs) is being curtailed in view of threat to public health occurring through microflora that are developing resistance to antibiotics. This risk has driven European Union and other countries to withdraw authorization of in-feed antibiotics since 1997. Removal of AGPs resulted in substantial increase infections in poultry. As a consequence, the poultry industry needs to find alternatives to antibiotics in order to stem the effects of infection. One comparable alternative is natural sources of herbs and medicinal plants, which later known as phytobiotics. For the last 15 years, these alternatives have been increasingly claimed to increase enteric health, stimulate digestive system, and enhance growth performance. It was reported that turmeric (Curcuma longa Linn.) belongs to such class of medicinal plant and may be an alternative to antibiotics in poultry production. In this review, the responses of poultry to diets supplemented with turmeric on growth performance, egg production, health status, and carcass characteristic were briefly discussed. Keywords: Turmeric, non-antibiotic feed additive, poultry production